Photomorphogenic modulation of water stress in tomato (Solanum lycopersicum L.): the role of phytochromes A, B1, and B2 - D'Amico-Damiao, V. [UNESP]; Cruz, E. J. R. [UNESP]; Gavassi, M. A. [UNESP]; Santos, D. M. M. [UNESP]; Melo, H. C.; Carvalho, R. F. [UNESP] (Headley Brothers Ltd, 2015)
Phytochromes are red/far-red light photoreceptors that mediate a variety of photomorphogenic processes in plants, from germination to flowering. In addition, there is evidence that phytochromes are also part of the stress signalling response, especially in response to water deficit stress, which is the major abiotic factor limiting plant growth and crop productivity worldwide. In this study, we used the phyA (far red-insensitive; fri), phyB1 (temporary red-insensitive; tri) and phyB2 mutants of tomato (Solanum lycopersicum L.) to study the roles of these three phytochromes in drought stress responses. Compared to wild type (WT) plants grown under water-deficit stress conditions, the fri, tri, and phyB2 mutants did not exhibit altered dry weights, leaf areas, stomatal densities, or stomatal opening. The stomatal conductance of all three mutants was severely reduced under both fully-hydrated and water-deficit conditions. Although relative water contents did change after drought stress in each mutant, the most significant reduction in water potential during water stress was observed in the fri mutant. However, this mutant returned its water status to WT levels during rehydration. Although the phyB2 mutant lost more water from detached leaves during abscisic acid (ABA) treatment, phyB2 behaved like WT plants, indicating that this mutant was not insensitive to ABA. Overall, these results indicate that the phytochromes phyA, phyB1, and phyB2 modulate drought stress responses in tomato.